Education in Emergencies Toolkit - Save The Children (2017)
The EiE Toolkit is part of the EiE Essential Resource Pack. It provides detailed guidance and a systematic and tools-based approach to analysing EiE needs, designing and implementing programmes. The Toolkit includes step-by-step guidance for selecting and sequencing interventions according to context. The toolkit is part of an EiE Essential Resource Pack, which includes a Framing Document and an online library (see below).

Tiyende! Let’s Walk! - Save the Children (2017)
Singilton Phiri Interactive Radio Instruction Specialist Save the Children in Malawi June 16, 2017 Before the introduction of sponsorship in rural Zomba in Malawi, walking...Read the full article...